Meiocyte Isolation by INTACT and Meiotic Transcriptome Analysis in Arabidopsis - Barra, Lucia; Termolino, Pasquale; Aiese Cigliano, Riccardo; Cremona, Gaetana; Paparo, Rosa; Lanzillo, Carmine; Consiglio, Maria Federica; Conicella, Clara (Frontiers in Plant Science, 2021)
INTACT is a method developed to isolate cell-type specific nuclei that are tagged through in vivo biotin-labeling of a nuclear targeting fusion (NTF) protein. In our work, INTACT was used to capture nuclei of meiocytes and to generate a meiotic transcriptome in Arabidopsis. Using the promoter of AtDMC1 recombinase to label meiotic nuclei, we generated transgenic plants carrying AtDMC1::NTF along with biotin ligase enzyme (BirA) under the constitutive ACTIN2 (ACT2) promoter. AtDMC1-driven expression of biotin-labeled NTF allowed us to collect nuclei of meiocytes by streptavidin-coated magnetic beads. Nuclear meiotic transcriptome was obtained by RNA-seq using low-quantity input RNA. Transcripts grouped into different categories according to their expression levels were investigated by Gene Ontology Enrichment Analysis (GOEA). The most enriched GO term ‘DNA demethylation’ in mid/high expression class suggests that this biological process is particularly relevant to meiosis onset. The majority of known meiotic genes was distributed in the classes of mid/high and high expression. Meiotic transcriptome was compared with public available transcriptomes from other tissues and cell types in Arabidopsis. The expression value of meiotic genes was higher in the isolated meiocytes compared to the other tissues/cell types with the exception of floral bud and meristem. Expression network analysis revealed gene modules related to meiosis as well as candidate genes with a potential meiotic role.